CYP3A5 genotype has an impact on the metabolism of the HIV protease inhibitor saquinavir - Josephson, Filip; Allqvist, A.; Janabi, M.; Sayi, J.; Aklillu, Eleni; Jande, M.; Mahindi, M.; Burhenne, Jürgen; Bottiger, Y.; Gustafsson, L. L.; Haefeli, Walter E.; Bertilsson, L. (Clinical pharmacology & therapeutics, 2007)
CYP3A is the main enzyme subfamily involved in the metabolism of the HIV protease-inhibitor saquinavir. We hypothesized that individuals homozygous for CYP3A5*1 might have a higher oral clearance of saquinavir, compared with subjects lacking functional CYP3A5 alleles. A single-dose pharmacokinetic trial of saquinavir soft gel capsules, 1,200 mg, was performed in 16 black Tanzanian healthy volunteers with two functional CYP3A5 alleles (*1/*1) and in 18 volunteers without functional CYP3A5 alleles (both alleles being either *3, *6, or *7). The median area under the plasma concentration-time curve (AUC)0-24 reached among subjects with two functional alleles was 1,410 ng h/ml (interquartile range (IQR) 826-1,929), whereas it was 2,138 ng h/ml (IQR 1,380-3,331) in subjects without (P=0.0533, Mann-Whitney U-test). The median ratio of saquinavir over its M2 plus M3 hydroxy metabolites in urine was 64 (IQR 52-73) in subjects with two functional alleles, whereas it was 145 (IQR 89-181) in those without (P=0.000078, Mann-Whitney U-test). In conclusion, saquinavir is metabolized by CYP3A5. The median AUC0-24 for saquinavir among individuals with two functional CYP3A5 alleles was 34% lower than among those with no functional alleles. To clarify the clinical importance of the CYP3A5 polymorphism, further studies should be conducted on saquinavir, dosed to steady state, in the presence of ritonavir boosting. Clinical Pharmacology & Therapeutics (2007) 81, 708-712. doi:10.1038/sj.clpt.6100117; published online 28 February 2007
Gesehen am 12.05.2021